OPTIMIZATION OF GENOMIC DNA EXTRACTION PROTOCOL FOR MOLECULAR PROFILING OF BANANA / PLANTAIN (MUSA SPECIES) - Romana Siddique (European Scientific Journal, ESJ, 2014)
Extraction of pure and high molecular weight genomic DNA (deoxyribonucleic acid) is a prerequisite for genetic analysis of plants. However, the presence of polysaccharides and polyphenols in plants represent a great challenge as it interferes the isolation of pure DNA and downstream reactions like PCR amplification. For this species, standard protocols do not produce high quality PCR amplifiable DNA. Here, in this study, an optimized protocol based on the standard CTAB (cetyl trimethyl ammonium bromide) protocol is described. The major changes in the optimized protocol are the addition of antoxidant compounds-namely polyvinyl pyrrolidone (PVP) and 2-mercaptoethanol, in the extracton buffer; the increasing of CTAB (3%,w/v) and sodium chloride (2M) concentration; and an extraction with organic solvents( phenol and chloroform). The yield of extracted DNA ranged from 150-200 μg / μl and the A260/A280 value was between 1.7-1.8 indicating minimal levels of contamination. Thus this protocol proved amenable for PCR and is suitable for further work on diversity analysis of Musaceae species.